Phenotypes and Genotypes of Erythromycin-Resistant Streptococcus pyogenes Strains in Italy and Heterogeneity of Inducibly Resistant Strains - Giovanetti, Eleonora (American Society for Microbiology, 1999)
A total of 387 clinical strains of erythromycin-resistant (MIC, ≥1 μg/ml) Streptococcus pyogenes, all isolated in Italian laboratories from 1995 to 1998, were examined. By the erythromycin-clindamycin double-disk test, 203 (52.5%) strains were assigned to the recently described M phenotype, 120 (31.0%) were assigned to the inducible macrolide, lincosamide, and streptogramin B resistance (iMLS) phenotype, and 64 (16.5%) were assigned to the constitutive MLS resistance (cMLS) phenotype. The inducible character of the resistance of the iMLS strains was confirmed by comparing the clindamycin MICs determined under normal testing conditions and those determined after induction by pregrowth in 0.05 μg of erythromycin per ml. The MICs of erythromycin, clarithromycin, azithromycin, josamycin, spiramycin, and the ketolide HMR3004 were then determined and compared. Homogeneous susceptibility patterns were observed for the isolates of the cMLS phenotype (for all but one of the strains, HMR3004 MICs were 0.5 to 8 μg/ml and the MICs of the other drugs were >128 μg/ml) and those of the M phenotype (resistance only to the 14- and 15-membered macrolides was recorded, with MICs of 2 to 32 μg/ml). Conversely, heterogeneous susceptibility patterns were observed in the isolates of the iMLS phenotype, which were subdivided into three distinct subtypes designated iMLS-A, iMLS-B, and iMLS-C. The iMLS-A strains (n = 84) were highly resistant to the 14-, 15-, and 16-membered macrolides and demonstrated reduced susceptibility to low-level resistance to HMR3004. The iMLS-B strains (n = 12) were highly resistant to the 14- and 15-membered macrolides, susceptible to the 16-membered macrolides (but highly resistant to josamycin after induction), and susceptible to HMR3004 (but intermediate or resistant after induction). The iMLS-C strains (n = 24) had lower levels of resistance to the 14- and 15-membered macrolides (with erythromycin MICs increasing two to four times after induction), were susceptible to the 16-membered macrolides (but resistant to josamycin after induction), and remained susceptible to HMR3004, also after induction. The erythromycin resistance genes in 100 isolates of the different groups were investigated by PCR. All cMLS and iMLS-A isolates tested had the ermAM (ermB) gene, whereas all iMLS-B and iMLS-C isolates had the ermTR gene (neither methylase gene was found in isolates of other groups). The M isolates had only the macrolide efflux (mefA) gene, which was also found in variable proportions of cMLS, iMLS-A, iMLS-B, and iMLS-C isolates. The three iMLS subtypes were easily differentiated by a triple-disk test set up by adding a josamycin disk to the erythromycin and clindamycin disks of the conventional double-disk test. Tetracycline resistance was not detected in any isolate of the iMLS-A subtype, whereas it was observed in over 90% of both iMLS-B and iMLS-C isolates.